The Perception of Facial Emotional Change in Social Anxiety: An ERP Study - Zhang, Qi; Ran, Guangming; Li, Xueping (Frontiers in Psychology, 2018)
Social anxiety is one of psychological symptoms most commonly occurring in social interaction. Although previous behavioral research has investigated the neutral-angry facial emotional change in social anxiety, none of the previous studies, however, has directly investigated the angry-neutral facial emotional change. Furthermore, less is known about the neural correlates of the facial emotional changes in social anxiety. The main goal of the present study was to explore the perception of facial emotional changes in social anxiety individuals, using high temporal resolution event-related potential (ERP) techniques. Behaviourally, accuracy was lower in the angry-neutral than neutral-neutral facial emotional change trials. Neurally, we found larger N170 amplitudes in angry-neutral than neutral-neutral facial emotional change trials for HSA participants, probably reflecting that they may engage in more analytical processing of different facial elements. Interestingly, HSA participants showed smaller P200 left hemisphere amplitudes in the angry-neutral compared to neutral-neutral facial emotional change trials, which suggested that they might have difficulties in the processing of emotion evaluation when they encountered these facial emotional changes. Finally, the LPP amplitudes in the neutral-angry and angry-neutral facial emotional change trials were smaller than those in the neutral-neutral facial emotional change trials, regardless of the social anxiety. These results suggest that the social anxiety influences the facial emotional changes mainly at an earlier stage of processing.